A Discrimination Method and Experimental Study for Predicting the Failure Strength of Saturated Sandstone Based on RVSD - Rongpeng Ren; Chi Li; Xiang Wu; Ruizhou Yang; XiaoYan Yang; Xianfeng Li; Yanchao Wang; Bo Yin (Shock and Vibration)
The Ordos coalfield contains shallowly buried coal seams, with sandstones in the overlying strata. Mining activities induced extensive fissures in the overlying rock and on the surface; thus, groundwater and surface water migrated through these fissures, accumulated within the mines and working faces, and diminished the surrounding rock strength. To reveal the failure patterns of the overlying sandstones and to explore a reliable method for monitoring rock layers and providing early disaster warnings, sandstones from the No. 2-3 coal seam in the Naoerhao Coal Mine were studied. With electrical resistivity and acoustic emission data acquired during the loading processes, experiments were conducted on the sandstones from the coal seam roof in both dry and water-saturated states. A method for predicting the failure strength of the water-saturated sandstones using the response of the resistivity standard deviation (RVSD) was developed. The results indicated that (1) the mechanical properties of the sandstone samples decreased significantly after water saturation; (2) a very strong correlation was observed among the acoustic emission, electrical resistivity, and stress during the loading process of the water-saturated samples; (3) introducing the RVSD to determine the rock closure strength and its combination with the corresponding stress level relative to the peak stress was an effective way to estimate the peak strength of the rock samples; and (4) based on the change in the number of acoustic emission hits within a unit of time, the locations of the precursor points to failure for sandstone were determined. Our proposed method for determining the characteristic points during the loading process of rock samples conforms to the principles of electrical resistivity and acoustic emission testing and can be easily adopted. This study can provide a reference for early warning systems for the sandstone roof failure in shallowly buried coal seams.